Interleukin-2 receptor (Tac antigen) expressed on adult T cell leukemia cells. - Uchiyama, T (1985)
We studied the expression of the interleukin-2 (IL-2) receptor and the proliferative response to exogenous IL-2 of peripheral blood leukemic cells from patients with adult T cell leukemia (ATL) in order to see whether IL-2 receptor expressed on ATL cells is different from normal IL-2 receptor and whether it plays a role in the neoplastic growth in ATL. Peripheral blood leukemic cells from 42 patients with ATL examined expressed IL-2 receptors that were detected by anti-Tac monoclonal antibody when examined immediately after the separation of cells or after the culture for 24 or 48 h. The number of anti-Tac binding sites ranged from 3,100 to 11,400 in fresh cells and from 3,600 to 96,000/cell in short-term cultured leukemic cells, whereas phytohemagglutinin-P (PHA-P)-stimulated normal T cells exhibited 6,900-35,000 anti-Tac binding sites per cell. ATL-derived and human T cell leukemia/lymphoma virus, type I (HTLV-I)-infected cell lines such as MT-1 and Hut102 expressed a much higher number of anti-Tac binding sites. Leukemic cells from 15 patients with ATL examined showed no or very poor proliferative response to various concentrations of immunoaffinity-purified IL-2, although they expressed Tac antigen (Ag). Radiolabeled IL-2 binding experiments demonstrated that ATL leukemic cells could bind IL-2, and they expressed both high and low affinity IL-2 receptors, although the number of high affinity IL-2 receptor was much less than that of low affinity IL-2 receptor and that of anti-Tac binding sites. In contrast, leukemic T cells from a patient with T cell chronic lymphocytic leukemia (CLL), in whom HTLV-I infection was not demonstrated, responded as well as PHA-P-stimulated normal T cells, and their IL-2 receptors, unlike ATL cells, were modulated (down regulated) by anti-Tac antibody. No differences were noted between ATL cells and normal activated T cells in one-dimensional sodium dodecyl sulfate polyacrylamide gel electrophoresis analysis of the IL-2 receptor. Thus, leukemic cells in ATL spontaneously and continuously express IL-2 receptor, which appears to be abnormally regulated and unresponsive to IL-2. These results, taken together with those on normal IL-2 receptors on HTLV-I-negative T-CLL cells, suggest that abnormal expression of the IL-2 receptor in ATL is closely associated with HTLV-I infection and may play a role in the neoplastic growth of ATL cells.